Jensen's Functionals on Time Scales. (4th December 2012) - Anwar, Matloob; Bibi, Rabia; Bohner, Martin; Pečarić, Josip
Abstract : We consider Jensen's functionals on time scales and discuss its properties and applications. Further, we define weighted generalized and power means on time scales. By applying the properties of Jensen's functionals on these means, we obtain several refinements and converses of Hölder's inequality on time scales.